Ecommerce risk management: analysing the case Vietnam Airlines incident - Quyet, Chu Ba; Cuong, Hoang Cao (Open Science Journal, 2017)
E-Commerce is the purchase and sale of goods, services and exchange of information based on communications networks and the Internet. Information, information systems, computers, computer networks, and other electronic means play an especially important role. These objects are valuable assets and targeted attacks by cybercriminals. E-commerce risk management is to protect the development of e-commerce. It includes setting information security objectives, assessing vulnerabilities, threats and attacks, and selecting countermeasures. The paper presents the theory of e-commerce risk management, analysing the Vietnam Airlines e-commerce risk management case, using the DREAD model. The paper provides the discussions and short recommendations to other enterprises in e-commerce risk management nowadays.